Lambertella pyrolae (Rutstroemiaceae, Ascomycota), a new species from Japan - Zhao, Yan-Jie; Hosoya, Tsuyoshi; Shirouzu, Takashi; Kakishima, Makoto; Yamaoka, Yuichi (Phytotaxa, 2013)
Lambertella pyrolae sp. nov. occurring on decayed leaves of Pyrola incarnata is described, illustrated, and compared with morphologically similar taxa. The diagnostic characters of L. pyrolae are: elongate-elliptic to fusoid ascospores, the ascal apex not stained by Melzer’s reagent, presence of hairs, and ascospore pigmentation occurring before discharge.